An ice‐obligate seabird responds to a multi‐decadal decline in Arctic sea ice - George J. Divoky; Pierre‐Loup Jan; Christophe Barbraud (Ecosphere)
Abstract The Arctic has experienced greatly decreased sea ice and increased ocean temperatures in recent decades but there is a paucity of biological time‐series data allowing assessment of resulting temporal variation in the region's marine ecosystems. Seabirds, as highly mobile and highly visible, upper trophic‐level predators, can be valuable monitors of modifications in marine ecosystems, especially for regions lacking commercial fisheries or regular oceanographic sampling. Since 1975, we have studied annually an Arctic Alaskan colony of Mandt's black guillemot (Cepphus grylle mandtii), an ice‐obligate diving seabird, specializing on Arctic cod (Boreogadus saida), the primary forage fish of the ice‐associated cryopelagic ecosystem. Using multi‐state capture–mark–recapture models, matrix population models, and perturbation analysis, we quantified the environmental and demographic drivers of population change from 1980 to 2019 for the individually marked population. The colony increased rapidly, from <20 to >200 breeding pairs from 1975 to 1990 in response to increased availability of nesting cavities, before experiencing intermittent declines to <50 pairs in 2021. Immigration and apparent survival were the primary demographic parameters affecting population growth with sea ice extent in late summer and fall the primary environmental driver. The initial growth occurred during a period of primarily negative winter Arctic Oscillations (WAO) and extensive summer sea ice. The decline began when an extremely positive WAO in 1989/1990 initiated changes in atmospheric and oceanographic circulation causing major reductions in summer sea ice throughout the region. The three‐decade decline in the population saw plateaus or minor growth with increasing frequency of negative WAOs and increasing declines following two previously identified “tipping points” in sea ice loss. Breeding success at the study colony declined with decreased availability of Arctic cod due to sea ice loss and increasing sea surface temperature and is presumed to have occurred at the source colonies for immigrants where similar oceanographic changes were occurring. Quasi‐extinction of the colony (reduction to <25 pairs) is predicted within the next two decades. The sensitivity of Mandt's black guillemot to multi‐decadal changes in the Arctic's cryopelagic ecosystem makes it an excellent sentinel species for the region with its recent collapse having dire implications for the Arctic Ocean's constituent species.